Pengaruh Pelatihan Quantum Learning Untuk Mengatasi Learning Loss Siswa Pasca Pandemi Covid 19 - Tasha Dwilamiisa Putri Dwilamiisa; Vesty Dheacylia Ramadhani; Indah Dita Rinanti; Fidela Cahya Sandani; Frestise Mangkubumi (PUSAKO : Jurnal Pengabdian Psikologi, 2022)
The covid-19 pandemic has left problems in various sectors, especially the education. Currently schools have started to open, meaning that life is back to normal where students return to learning in class with health protocols. During the transition from online learning to face-to-face learning, it becomes a difficult time for students because for almost 2 years students who have not studied online optimally tend to experience what is called learning loss, namely a condition of decline in the learning process or falling behind in learning. Students must catch up with the setbacks in the learning process due to the limitations of online learning. The way that can be done to deal with learning loss is to teach students effective learning strategies. One of the learning strategies such as quantum learning is effective in improving student learning outcomes. The activity offered is quantum learning training for students who experience learning loss due to the covid 19 pandemic. The training activity was carried out on December 1, 2021 in the hall of SMA Negeri 2 Pariaman. A pretest and posttest were given to 20 students. The results of the pretest and posttest showed Asymp. Sig. (2-tailed) of 0.000 which is less than the critical research limit of 0.05 (p < 0.05) which means that there is an effect of quantum learning training to overcome student learning loss after the covid 19 pandemic. This training was smooth and able to provide knowledge to students in overcoming learning loss and have motivation to learn.